Glucagon-like peptide-1: a new potential regulator for mesenchymal stem cells in the treatment of type 2 diabetes mellitus and its complication - Zi’an Shao; Xiaoguang Zhang; Junrong Cai; Feng Lu (Stem Cell Research & Therapy)
Abstract Glucagon-like peptide-1 is an enteric proinsulin hormone secreted by intestinal L-cells that orchestrates insulin secretion in a glucose-dependent manner. Renowned for preserving pancreatic β-cell mass, glucagon-like peptide-1 facilitates β-cell proliferation and inhibits apoptosis, while concurrently suppressing glucagon secretion from pancreatic α-cells, thereby exerting hypoglycemic effects. Recent in vitro and in vivo studies have clarified the benefits of combination therapy with glucagon-like peptide-1 and stem cells in Type 2 diabetes mellitus. Glucagon-like peptide-1 enhances the repair of type 2 diabetes mellitus-afflicted tissues and organs by modulating sourced mesenchymal stem cell differentiation, proliferation, apoptosis, and migration. Importantly, glucagon-like peptide-1 overcomes the detrimental effects of the diabetic microenvironment on transplanted mesenchymal stem cells by increasing the number of localized cells in stem cell therapy and the unstable efficacy of stem cell therapy. This review elucidates the molecular and cellular mechanisms through which glucagon-like peptide-1 regulates mesenchymal stem cells in the type 2 diabetes mellitus context and discuss its therapeutic prospects for type 2 diabetes mellitus and its associated complications, proposing a novel and comprehensive treatment paradigm.